Arbitration and litigation for Muslim minorities - Abdel Qawi, Hoda Abdel Hamid (Arab Journal for Sciences and Research Publishing, 2016)
Muslim minorities always need to enter the circle of research, because we find them living among societies that differ in their habits, customs and rulings. So they need special rules of arbitration and litigation for the arising disputes between them. This research explains the importance of the arbitration and litigation among the Muslim minorities, so as not heavily exposed to the country’s courts and the states in which they reside, to end the rivalries and disputes that arise between them. This shows the importance of the establishment of the Islamic centers and councils in the foreign countries to activate the role of the Mufti, arbitration and litigation without breaking any local laws in these countries, and also by showing the tolerance of Islam on the correct way and by the understandings of the ancestors of the Muslim nation. This research has an introduction, two sections and a conclusion as follows: The introduction contains the importance and the methodology of the research, and the previous studies. Then the research plan which contains: The origins of arbitration for Muslim minorities which has two subsections: Arbitration and its Islamic rules for minorities and minorities need to arbitration. The judiciary and the trials of minorities which has two subsections: the minority judiciary in lawsuits and family cases, the minority courts should punish for all crimes by simple punishments and not capital punishment. And finally the conclusion which contains the findings and recommendations.